ADVERSE SELECTION IN DYNAMIC MATCHING MARKETS. (3rd July 2012) - Kultti, Klaus; Mauring, Eeva; Vanhala, Juuso; Vesala, Timo
ABSTRACT We study the Akerlofian adverse selection problem in a dynamic matching model where the competitive situation varies across different meetings. The 'lemons principle' is shown to limit the high quality sales within a wider range of quality distributions than in the Walrasian benchmark. High quality goods can nevertheless be traded, albeit less frequently than the low quality goods. For certain quality distributions, there exists a 'partially pooling' steady state where high quality sellers are active whenever at least two buyers compete for the good. Otherwise, the model features cycles in a sense that high quality goods are traded only in non‐consecutive periods.